PENGARUH CITRA PASAR JUM’AT KARANGANYAR TERHADAP WORDS OF MOUTH (WOM) MELALUI CUSTOMER DELIGHT SEBAGAI VARIABEL MEDIASI - Untung Sri Widodo; Ernawati . (INFORMATIKA, 2014)
The purpose of this research is to analyze (1) effect of Friday market image to customer delight, (2) effect of Friday market image influence on positive WOM, (3) effect of customer delight influence on positive WOM, (4) indirect effect of Friday market image on positive WOM through customer delight as a mediation variables. The population of this research are all consumers of Friday market of Karanganyar. In this research amount of sample is 100 customers. Sampling method using snowball and accidental sampling. To test this hypothesis, researchers used a path analysis, while for data processing using SPSS Release 12. The results shows that (1) Friday market image has a significant effect on customer delight, thus H1 is supported; (2) Friday market image has no a significant and positive effect on WOM, thus H2 is not supported; (3) customer delight has a significant effect on positive WOM, thus H3 is supported; (4) customer delight mediates the effect of Friday market image on positive WOM, thus H4 is supported. Keywords : Friday market image, customer delight, positive WOM